2010
DOI: 10.1177/1553350610372378
|View full text |Cite
|
Sign up to set email alerts
|

Total Intracorporeal Anastomosis During Single-Port Laparoscopic Right Hemicolectomy for Carcinoma of Colon: A New Step Forward

Abstract: Single-port access right hemicolectomy with intracorporeal anastomosis is a feasible and safe technique when performed by experienced laparoscopic surgeons. This approach must follow the basic principles of laparoscopic right hemicolectomy to achieve the same oncological results. The advantages of a total intracorporeal anastomosis include that there is no need to enlarge the umbilical incision and that avoid traction of the pedicle of the mesenterium of the transverse colon during the extracorporeal anastomos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 9 publications
0
17
0
1
Order By: Relevance
“…While we utilized the Gelpoint device for this procedure, there are several other access devices available for single-incision surgery, some of which report improvements in triangulation that make the procedure technically easier. Additional techniques including use of transperitoneal stitch [19,25] and magnets [18] have also aided in retraction during dissection. If dissection is difficult and not progressing, an additional port can be placed for assistance without the requirement to convert to an open procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we utilized the Gelpoint device for this procedure, there are several other access devices available for single-incision surgery, some of which report improvements in triangulation that make the procedure technically easier. Additional techniques including use of transperitoneal stitch [19,25] and magnets [18] have also aided in retraction during dissection. If dissection is difficult and not progressing, an additional port can be placed for assistance without the requirement to convert to an open procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently reported single-incision operation in colorectal surgery has been right hemicolectomy. After first being described in 2008 [19,20], multiple case reports and series have demonstrated the safety and feasibility of right hemicolectomy [21][22][23][24][25][26][27][28][29]. Case-control studies of single-incision laparoscopic right colectomy have demonstrated the technique to be equivalent to conventional laparoscopic surgery with a small cosmetic benefit [30][31][32].…”
mentioning
confidence: 96%
“…Both retrospective and prospective analyses, as well as meta-analyses and systematic reviews have shown the technique to be safe and feasible when compared to standard laparoscopic techniques [19][20][21][22][23][24][25][26][27][28][29][30]. Case-control studies have also demonstrated equivalence, with a small cosmetic benefit [31][32][33].…”
Section: Introductionmentioning
confidence: 91%
“…Retraction of the appendix with transabdominal “sling” sutures through the mesoappendix is an example of a commonly used strategy in the early stages of SILS appendectomy [2]. More recently, innovative techniques evolved into more complex laparoscopic procedures including nephrectomy, splenectomy, adrenalectomy, and bowel resection with intracorporeal anastomosis [36]. …”
Section: Introductionmentioning
confidence: 99%